Metacompetences : how important for organizations? Analysis a survevy in Portugal - Pereira, Orlando P. (2013)
The models and variables leveraging productivity and the performance of corporate collaborators have been highly discussed in academic, economic and corporate fields. This paper is written according to this same spirit and aims at casting a critical view over the role played by meta-competences in the organizational structure. It simultaneously intends to reflect on strategic aspects of spirituality, such as the multiplicative variables of performance and productivity in organizations. Therefore, it is important to analyse the feeling graduates get from applying soft skills in corporate everyday life, since they are potential “collaborators” of these institutions. After hearing their mind, we have noticed that, though mainly positive, the results obtained reveal the need for a broader reflection, which might start in organizations and reach out to Universities, as this is the production and spreading point of global knowledge, the basic skills, foundations of a future organizational collaborator. We present the result of a survey in Portugal.